Murine maternal dietary restriction affects neural Humanin expression and cellular profile. Issue 5 (15th December 2019) - Baldauf, Claire; Sondhi, Monica; Shin, Bo‐Chul; Ko, Young Eun; Ye, Xin; Lee, Kuk‐Wha; Devaskar, Sherin U.
Abstract: To understand the cellular basis for the neurodevelopmental effects of intrauterine growth restriction (IUGR), we examined the global and regional expression of various cell types within murine ( Mus musculus ) fetal brain. Our model employed maternal calorie restriction to 50% daily food intake from gestation day 10–19, producing IUGR offspring. Offspring had smaller head sizes with larger head:body ratios indicating a head sparing IUGR effect. IUGR fetuses at embryonic day 19 (E19) had reduced nestin (progenitors), β‐III tubulin (immature neurons), Glial fibrillary acidic protein (astrocytes), and O4 (oligodendrocytes) cell lineages via immunofluorescence quantification and a 30% reduction in cortical thickness. No difference was found in Bcl‐2 or Bax (apoptosis) between controls and IUGR, though qualitatively, immunoreactivity of doublecortin (migration) and Ki67 (proliferation) was decreased. In the interest of examining a potential therapeutic peptide, we next investigated a novel pro‐survival peptide, mouse Humanin (mHN). Ontogeny examination revealed highest mHN expression at E19, diminishing by postnatal day 15 (P15), and nearly absent in adult (3 months). Subanalysis by sex at E19 yielded higher mHN expression among males during fetal life, without significant difference between sexes postnatally. Furthermore, female IUGR mice at E19 had a greater increase in cortical mHN versus the male fetus over their respective controls. We conclude that maternal dietary restriction‐associated IUGR interferes with neural progenitors differentiating into the various cellular components populating the cerebral cortex, and reduces cerebral cortical size. mHN expression is developmental stage and sex specific, with IUGR, particularly in the females, adaptively increasing its expression toward mediating a pro‐survival approach against nutritional adversity. Abstract : Neuroprotective, anti‐apoptotic peptide Humanin is expressed in fetal brain with specific localization pattern and ontogeny. Maternal dietary restriction associated intra‐uterine growth restriction alters fetal brain Humanin expression in a sex and location specific manner while diminishing fetal neural progenitors, neurons, and glia.